P23 Re-development of a pulmonary rehabilitation education programme. (12th November 2019) - Bourne, C; Gardiner, N; Singh, S
Abstract : Introduction: Patient education is considered integral to a comprehensive pulmonary rehabilitation (PR) programme. Historically, there has been limited evidence on which to guide optimal design and delivery. Following the ATS/TSANZ/CTS/BTS Workshop (The American Thoracic Society (ATS) Workshop on Education in Pulmonary Rehabilitation for Individuals with Chronic Obstructive Pulmonary Disease (COPD)) in 2016, we recognised a need to update our current PR education programme. Aim: To re-develop and optimise delivery of the educational component of PR with a view toward enhancing the effectiveness of this component. Methods: We used the ATS/TSANZ/CTS/BTS Workshop Report: COPD Education in Pulmonary Rehabilitation 1 to structure our education re-development alongside Bloom's Taxonomy of Learning, Teaching and Assessing 2 . We created objectives based on learner needs and formulated a delivery strategy (consisting of content and method; figure 1). Results: 12 PR education sessions have been re-developed and are currently being implemented. Delivery has been cascaded using the following method, once each session has been finalised by the lead author of that session: Observation of the new session Practice delivery of the new session Checked for fidelity to session plan Staff received additional group training in facilitating groups due to the more interactive nature of the new sessions. Conclusions: It is feasible to use the ATS/TSANZ/CTS Workshop Report to structure a PR education re-development. The final elements of the re-development process are to gain patient and staff feedback on the new sessions, to complete programme content and delivery. Following on from this we intend to evaluate the new programme of education. References: Blackstock FC, Lareau SC, Nici L, ZuWallack R, Bourbeau J, Buckley M, Durning S, Effing TW, Egbert E, Goldstein R, Kelly W, Lee A, Meek PM, Schuwirth L, Singh S. Chronic obstructive pulmonary disease education in pulmonary rehabilitation an official american thoracic society/thoracic society of australia and new zealand/canadian thoracic society/british thoracic society workshop report. Ann Am Thorac Soc 2018;15(7):769–784. Anderson L, Krathwohl DR, Bloom BS. ( 2001). A taxonomy for learning, teaching, and assessing: a revision of Bloom's taxonomy of educational objectives . Pearson .